Electrochemical oxidation of vitamin e (α-toh) inside artificial lipid multilayers. - Lau, Charmaine. (2010)
α-Tocopherol is electrochemically converted into α-tocopherol quinone via an intermediate α-tocopherol phenoxonium cation. It is a chemically irreversible process which occurs readily in the presence of water. This -2e-/-2H+ oxidation reaction was examined by conducting electrochemical experiments with α-tocopherol (vitamin E) deposited on electrode surfaces. Experiments involving the inclusion of α-tocopherol into lecithin multilayers were conducted to determine whether the oxidation reaction occurred within model lipid bilayer membranes. The consequence of the use of Nafion, a proton exchange membrane, together with the α- tocopherol/lecithin multilayer film on the electrodes was examined and compared to the situation when only the α-tocopherol/lecithin multilayer was used. Further comparisons were studied to identify the effects of the lipid multilayer structure, when the coated α-tocopherol films were prepared by dissolution in organic solvents (MeCN) and subjected to measurements in aqueous buffer solutions. Experiments carried out electrochemically utilised variations in pH and scan rates to study their effects on the α-tocopherol conversion mechanism via comparison of the cyclic voltammograms obtained. An α-tocopherol quinone model compound incorporated in the lecithin multilayer structure was also used, together with Nafion coatings on the electrode, to affirm the occurrence of the chemically reversible conversion of α-tocopherol quinone to α-tocopherol hydroquinone in cases where the α- tocopherol/lecithin multilayer system was applied instead. At faster scan rates and where pH < 13, it was observed that the α-tocopherol quinone/hydroquinone conversion process occurred together with the appearance of the phenoxonium cation intermediate, which is then reduced back to the α-tocopherol starting material via the 2 e-/ H+ process. The inclusion of Nafion into the coatings on the electrode was observed to provide more consistent results and well-defined peaks for interpretation and analytical purposes.